The Role of Extracellular Vesicles in Modulating the Host Immune Response during Parasitic Infections - Montaner, Sergio; Galiano, Alicia; Trelis, María; Martin-Jaular, Lorena; del Portillo, Hernando A.; Bernal, Dolores; Marcilla, Antonio (Frontiers in Immunology, 2014)
Parasites are the cause of major diseases affecting billions of people. As the inflictions caused by these parasites affect mainly developing countries, they are considered as neglected diseases. These parasitic infections are often chronic and lead to significant immunomodulation of the host immune response by the parasite, which could benefit both the parasite and the host and are the result of millions of years of co-evolution. The description of parasite extracellular vesicles (EVs) in protozoa and helminths suggest that they may play an important role in host-parasite communication. In this review, recent studies on parasitic (protozoa and helminths) EVs are presented and their potential use as novel therapeutical approaches is discussed.